Dispersion of Echinococcus granulosus eggs from infected dogs under natural conditions in Patagonia, Argentina - Sánchez Thevenet, P. (2019)
Cystic echinococcosis caused by Echinococcus granulosus is a major zoonosis of public health significance in the Patagonian region of Argentina. This investigation sought to test the hypothesis that the persistence and dispersion of the parasite eggs can be explained by physical and meteorological parameters along with final host infection and behaviour. This observational study was carried out over a five-year period within an enclosure where two dogs harbouring a worm burden ranging from 100 to 1000 mature adult E. granulosus, as well as two uninfected dogs, had previously been kept for six months. Environmental canine faeces, topsoil, pond water, and sediment samples were examined to control for the presence of eggs and coproantigens of the parasite using microscope-based techniques and copro-ELISA plus copro-Western Blot tests. The parasite eggs were detected up to 41 months later in faeces from infected dogs, soil and sediment, and coproantigen tests remained positive for up to 70 months in faeces. Overall, parasite eggs were found within a maximum distance of 115 m from the contaminated dog faeces deposition site. Our findings indicate that under Patagonian environmental conditions, egg persistence and dispersion seem to be related to the worm burden and habits of the infected dog, to prevailing wind direction and to the existence of low bushes as well as natural bodies of water. The present study is the first to provide direct evidence of interaction between bioclimatic conditions and E. granulosus egg dispersion under Patagonian field conditions.